2022
DOI: 10.3389/fnhum.2022.940845
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory beta/alpha band modulations: A potential biomarker of functional language and motor recovery in chronic stroke?

Abstract: Stroke remains one of the leading causes of various disabilities, including debilitating motor and language impairments. Though various treatments exist, post-stroke impairments frequently become chronic, dramatically reducing daily life quality, and requiring specific rehabilitation. A critical goal of chronic stroke rehabilitation is to induce, usually through behavioral training, experience-dependent plasticity processes in order to promote functional recovery. However, the efficiency of such interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…Our findings showed an increase in alpha and beta bands in both lesioned and non-lesioned hemispheres, but such improvement was not over sham. Enhancement of high-frequency bands (alpha and beta) over the frontal and central have been reported after motor training during post-stroke recovery phases, which are related to motor relearning and recovery process [ 7 , 44 , 51 53 ], reflecting a better motor recovery [ 44 , 54 ]. Enhancement of high-frequency bands (alpha and beta) have also been reported to increase following anodal tDCS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings showed an increase in alpha and beta bands in both lesioned and non-lesioned hemispheres, but such improvement was not over sham. Enhancement of high-frequency bands (alpha and beta) over the frontal and central have been reported after motor training during post-stroke recovery phases, which are related to motor relearning and recovery process [ 7 , 44 , 51 53 ], reflecting a better motor recovery [ 44 , 54 ]. Enhancement of high-frequency bands (alpha and beta) have also been reported to increase following anodal tDCS.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying the modulation of high-frequency bands is controversial [ 57 ]. However, a possible mechanism may involve the interaction between cellular GABAergic-glutamatergic neurons in the cortex [ 44 ]. GABA concentration influences alpha and beta bands [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 , 37 ] Previous research has suggested that alterations in alpha and beta oscillations could reflect the intricate mechanisms of cortical excitatory-inhibitory balance, potentially serving as indicators of motor recovery post-stroke. [ 38 ] For instance, Cassidy utilized lasso regression to evaluate the extent of motor recovery during subacute stroke, identifying the high beta (20–30 Hz) and alpha bands (8–12 Hz) as significant contributors to the model, with both positive and negative associations with motor outcomes. [ 7 ] Our study confirms the specific modulatory effects of EA stimulation within the alpha and beta bands of the brain networks.…”
Section: Discussionmentioning
confidence: 99%
“…Spectral analysis is a mathematical technique that utilizes the Fourier transform to analyze the frequency content of signals, with the most common approach being the analysis of the variation of power spectral density (PSD) or relative power (RP) of a frequency band of interest. ERD, on the other hand, involves the decrease in neural oscillation power in response to a time-locked event, such as MI, and has been shown to promote motor recovery and rehabilitation by facilitating changes in brain connections and the development of new neural pathways 3 , 17 , 18 . However, it is important to note that these methods do not provide a complete understanding of the complex reorganization and communication patterns within the brain network.…”
Section: Introductionmentioning
confidence: 99%